Markets of dispossession NGOs, economic development, and the state in Cairo - Elyachar, Julia (Duke Univ. Press, 2005)
What happens when the market tries to help the poor? In many parts of the world today, neoliberal development programs are offering ordinary people the tools of free enterprise as the means to well-being and empowerment. Schemes to transform the poor into small-scale entrepreneurs promise them the benefits of the market and access to the rewards of globalization. Markets of Dispossession is a theoretically sophisticated and sobering account of the consequences of these initiatives. Julia Elyachar studied the efforts of bankers, social scientists, NGO members, development workers, and state officials to turn the craftsmen and unemployed youth of Cairo into the vanguard of a new market society based on microenterprise. She considers these efforts in relation to the alternative notions of economic success held by craftsmen in Cairo, in which short-term financial profit is not always highly valued. Through her careful ethnography of workshop life, Elyachar explains how the traditional market practices of craftsmen are among the most vibrant modes of market life in Egypt. Long condemned as backward, these existing market practices have been seized on by social scientists and development institutions as the raw materials for experiments in "free market" expansion. Elyachar argues that the new economic value accorded to the cultural resources and social networks of the poor has fueled a broader process leading to their economic, social, and cultural dispossession.
Keywords: Wirtschaft; Urban poor -- Egypt -- Cairo; Entrepreneurship -- Egypt -- Cairo; Social networks -- Egypt -- Cairo; Business networks -- Egypt -- Cairo; New business enterprises -- Egypt -- Cairo; Non-governmental organizations -- Egypt -- Cairo; Nichtstaatliche Organisation; Wirtschaftliche Lage; Armut; Stadtbevölkerung; Cairo (Egypt) -- Economic conditions; Kairo